Additive effects of physical exercise and environmental enrichment on adult hippocampal neurogenesis in mice - Fabel, Klaus; Wolf, Susanne; Ehninger, Dan; Babu, Harish; Galicia, Perla; Kempermann, Gerd (Frontiers in Neuroscience, 2009)
Voluntary physical exercise (wheel running, RUN) and environmental enrichment (ENR) both stimulate adult hippocampal neurogenesis but do so by different mechanisms. RUN induces precursor cell proliferation, whereas ENR exerts a survival-promoting effect on newborn cells. In addition, continued RUN prevented the physiologically occurring age-related decline in precursor cell in the dentate gyrus but did not lead to a corresponding increase in net neurogenesis. We hypothesized that in the absence of appropriate cognitive stimuli the potential for neurogenesis could not be realized but that an increased potential by proliferating precursor cells due to RUN could actually lead to more adult neurogenesis if an appropriate survival-promoting stimulus follows the exercise. We thus asked whether a sequential combination of RUN and ENR (RUNENR) would show additive effects that are distinct from the application of either paradigm alone. We found that the effects of 10 days of RUN followed by 35 days of ENR were additive in that the combined stimulation yielded an approximately 30% greater increase in new neurons than either stimulus alone, which also increased neurogenesis. Surprisingly, this result indicates that although overall the amount of proliferating cells in the dentate gyrus is poorly predictive of net adult neurogenesis, an increased neurogenic potential nevertheless provides the basis for a greater efficiency of the same survival-promoting stimulus. We thus propose that physical activity can “prime” the neurogenic region of the dentate gyrus for increased neurogenesis in the case the animal is exposed to an additional cognitive stimulus, here represented by the enrichment paradigm.